Edukasi Mengenai Pemanfaatan Minyak Jelantah Menjadi Sabun Cuci Piring di Kelurahan Joyosuran Surakarta - Jauza Helmi Irfani; Lia Noviana; Cornelia Dinda; Neeva Nama Shafira; Iva Aura Apriliana W; Gita Wanda Pratiwi; Shafira Khoirunnisa (Asosiasi Periset Bahasa Sastra Indonesia, 2024)
Cooking oil that has been heated three times is very dangerous for human health if reused, but if it is thrown away directly it can pollute the environment, such as blockages in sewer pipes, pollution of clean water, river pollution and soil pollution. This community service activity aims to increase motivation and equip residents, especially housewives, in processing cooking oil waste, which was previously liquid waste that could pollute the environment. This service activity includes several stages, namely the service team planning, coordinating with the PKK Chair in Joyusuran Village, socializing and the process of making soap products from used cooking oil. This activity simulates processing used cooking oil into solid laundry soap as an environmentally friendly product and can reduce environmental pollution due to disposal of used cooking oil.